Peluang Dan Tantangan Perbankan Syariah Di Tengah Maraknya Financial Technology (Fintech) Berbasis Pinjaman Online - Setiyowati, Arin; SM, Ainol Yaqin (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this research is to show the opportunities and obstacles that exist in Islamic banking in the midst of the development of online loan-based fintech which is widely used by the public due to the ease of applying for loans. This is different from financing in Islamic banking in terms of submitting financing which is not as easy and fast as that offered by fintech. This research uses a qualitative method with data collection techniques through literature study. From the data collected, researchers will compare the opportunities and challenges of Islamic banking in the midst of the development of online loan-based fintech. The results of this research indicate that the opportunity for Islamic banking is to be able to increase access to finance for the unreached public through collaboration with Islamic fintech, attracting, collecting and channeling funds at a broader level, and channeling digital-based Islamic financing. The challenges are in regulating and supervising fintech companies operating within the Islamic banking system, competition with conventional fintech that do not follow sharia principles, and the lack of public education about the differences between loans in Islamic banking and fintech online loans.